Effects of Monsoon on Groundwater Quality for Irrigation in Gohana Block of Haryana - Pradhan, S; Chandrasekharan, H; Sehgal, V K; Chakraborty, D; Jain, N; Kamble, K; Kamra, S K (Annals of Arid Zone, 2016)
Irrigation water quality plays an important role in influencing the agricultural sustainability particularly in arid and semi-arid tracts of the country where it is inevitable for the farmers to use the resources, even if of doubtful quality. The Gohana Block in Haryana, India, is selected to discuss the impact of monsoon on groundwater quality for irrigation where agriculture is the main livelihood of rural people and the groundwater is the main source of irrigation. To study the impact of monsoon on groundwater quality, sixty groundwater samples were collected from the study area; in June (pre-monsoon) and in November (post-monsoon) in 2006. The water amples were analyzed for pH, Ec, major cations (sodium, pqtassium, calcium, and magnesium), major anions (bicarbonate, chloride, sulphate and nitrate) and heavy metals (arsenic, cadmium, lead and nickel) using standard procedure. Specific irrigation water quality criteria like Sodium Adsorption Ratio (SAR), Residual Sodium Carbonate (RSC) and Mg/Ca ratio were computed from the above chemical parameters. The comparison of pre-monson and post-monsoon data showed marginal improvement in groundwater quality after monsoon. Key words: Groundwater quality, monsoon, Ec, SAR, RSC’, Mg/Ca ratio.